The Contribution of Criminal-Law Means to Saving the Sturgeon from the Danube and Black Sea - Tache Bocaniala (Journal of Danubian Studies and Research, 2016)
The protection of certain species of fauna and flora against overexploitation and rescuing some of them from extinction is mainly the concern of many institutions and organizations especially the NGOs. Among these species currently threatened with extinction include the wild sturgeons, ancient species, since the age of the dinosaurs. Given that Romania and Bulgaria are the only EU countries on whose territory there are populations of sturgeon breeders, in this study we aim rather at drawing an alarm signal in addition on the need of improving the juridical-criminal framework that would ensure the protection and rescue of sturgeons from extinction.